Pendidikan Islam dan Multikulturalisme di Indonesia - Sapirin Sapirin (Universitas Negeri Medan, 2020)
The plurality of Indonesian society can be seen from various sides in terms of race, ethnicity, culture, religion, socioeconomic groups and even in terms of political orientation. The diversity that is owned by the people of Indonesia is a distinct characteristic that is a priceless wealth. On the other hand, although diversity is a very prestigious thing, on the other hand it can be a potential that drives conflict and division. The concept of multicultural education has a significant problem that is concerned with religious understanding. If this is the emphasis, then in the teaching of Islam the teachings are those that deal with universal values as possessed by all religions. While it is understood for certain that in Islamic religious education taught is monotheism, jurisprudence, and morality karimah. Thus it can be understood that in Islamic religious education is very strongly based in fostering civilized humans. If we pay attention, multiculturalism education does not have a strong foundation in conceptualizing its educational goals. Compared to Islamic education the foundation is clearly based on the Koran, Sunnah and Ijtihad on the ulama. So it is clear that the goal of Islamic education is the formation of attitudes, of course at the social level it is part of multiculturalism education. The attitude here is praiseworthy behavior which is a reflection of Islamic education itself.